2012
DOI: 10.1103/physrevlett.109.097204
|View full text |Cite
|
Sign up to set email alerts
|

Core-Core Dynamics in Spin Vortex Pairs

Abstract: We investigate nanopillars in which two thin ferromagnetic particles are separated by a nanometer thin nonmagnetic spacer and can be set into stable spin vortex-pair configurations. We find that the previously unexplored limit of strong vortex core-core coupling can dominate the spin dynamics in the system. We observe experimentally and explain analytically and numerically how the 0.2 GHz gyrational resonance modes of the individual vortices are transformed into a 2 GHz collective rotational resonance mode in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 39 publications
1
38
0
2
Order By: Relevance
“…In the case of two vortices confined to an elliptical disk, the vortices have opposite chirality (c 1 = −c 2 ) in order to decrease the exchange energy of the disk. There have been several reports on vortex-vortex interactions in laterally [13][14][15][16][17][18][19] and longitudinally [20,21] separated disks. Studies on vortex pairs confined to a single disk are reported in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of two vortices confined to an elliptical disk, the vortices have opposite chirality (c 1 = −c 2 ) in order to decrease the exchange energy of the disk. There have been several reports on vortex-vortex interactions in laterally [13][14][15][16][17][18][19] and longitudinally [20,21] separated disks. Studies on vortex pairs confined to a single disk are reported in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…An effective interaction between vortex cores of disks was only observed if they approached each other at about 10 nm distance. 18 As VCs of both disks are moving nonsynchronously, there is a certain range of amplitudes and frequencies of a pulsed excitation at which cores meet each other. Micromagnetic simulation showed that in a system with the same geometrical parameters, VC of the big disk can take out the small disk from V state, only if VC is moving with velocity near critical value (V c % 300 m/s).…”
mentioning
confidence: 99%
“…(5) is approximate and yields the solution for the gyrotropic motion of the vortex core in the low-frequency (< 1 GHz) range. However, in recent theoretical studies [27][28][29][30] the modified Thiele equation was analyzed with regard to the terms of higherorder derivatives of the coordinate with respet to time:…”
Section: Collective Variables Technique In the Description Of The Vormentioning
confidence: 99%